(untitled) (Research, Society and Development, 2023)
The discussion on topics such as education and democracy has become increasingly common, in the academic context, the result of debates between researchers in the areas of social sciences, philosophical, political, legal, education and the like. The purpose of this article is to analyze variables related to education that can lead to a better quality in the democracy of certain countries. To do so, we sought a methodology based on a descriptive-quantitative approach, manifested through a cross-sectional observational study in 179 countries around the world. As an independent variable, in the statistical correlation tests, we used: freedom of expression, academic and cultural; freedom to research and teach; freedom of academic exchange and dissemination, index of academic freedom; and, freedom of discussion. In turn, as a dependent variable, data related to the democracy index were sought. The results show that the countries that have the best educational indexes are also included in those that are more democratic.